Efficacy and safety of dulaglutide in the treatment of type 2 diabetes: a comprehensive review of the dulaglutide clinical data focusing on the AWARD phase 3 clinical trial program. Issue 8 (15th May 2016) - Jendle, Johan; Grunberger, George; Blevins, Thomas; Giorgino, Francesco; Hietpas, Ryan T.; Botros, Fady T.
Summary: Dulaglutide (DU) is a once weekly glucagon‐like peptide‐1 receptor agonist (GLP‐1 RA) approved for the treatment of type 2 diabetes mellitus (T2DM). Glycaemic efficacy and safety characteristics of dulaglutide have been assessed in six Phase 3 studies in the AWARD program. The objective of this review article is to summarize these results from the six completed AWARD studies. At the primary endpoint, in five of the six studies, once weekly dulaglutide 1.5 mg was superior to the active comparator [exenatide, insulin glargine (two studies), metformin, and sitagliptin], with a greater proportion of patients reaching glycated hemoglobin A1c (HbA1c) targets of <7.0% (53.0 mmol/mol) and ≤6.5% (47.5 mmol/mol). Dulaglutide 1.5 mg was non‐inferior to liraglutide in AWARD‐6. Once weekly dulaglutide 0.75 mg was evaluated in five of these trials and demonstrated superiority to the active comparator in four of five AWARD studies (exenatide, glargine, metformin, and sitagliptin), and non‐inferiority to glargine in the AWARD‐2 study. Similar to other GLP‐1 receptor agonists, treatment with dulaglutide was associated with weight loss or attenuation of weight gain and low rates of hypoglycaemia when used alone or with non‐insulin‐secretagogue therapy. The most frequently reported adverse events were gastrointestinal, including nausea, vomiting, and diarrhea. The incidence of dulaglutide antidrug antibody formation was 1–2.8% with rare injection site reactions. In conclusion, dulaglutide is an effective treatment for T2DM and has an acceptable tolerability and safety profile. Copyright © 2016 John Wiley & Sons, Ltd.